1998
DOI: 10.1063/1.476731
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of internal rotation of methyl group with proton transfer in the S1 state of 5-methyltropolone

Abstract: A combined nuclear dynamics and electronic study of the coupling between the internal rotation of the methyl group and the intramolecular proton transfer in 5-methyltropoloneCoupling between the internal rotation of the methyl group and proton/deuteron transfer in jet-cooled 5-methyl-9hydroxyphenalenone(OH) and 5-methyl-9-hydroxyphenalenone(OD): Tunneling rate dependence of coupling potential Tunneling in jet-cooled 5-methyltropolone and 5-methyltropolone-OD. Coupling between internal rotation of methyl group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…From the theoretical point of view proton transfer in the ground electronic state is more easily tractable. Extensive experimental and theoretical studies have been reported for multidimensional proton tunneling in tropolone [3][4][5][6][7][8][9][10][11][12][13]. Vener et al [10] studied theoretically multidimensional proton tunneling in tropolone by using adiabatic separation of variables.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the theoretical point of view proton transfer in the ground electronic state is more easily tractable. Extensive experimental and theoretical studies have been reported for multidimensional proton tunneling in tropolone [3][4][5][6][7][8][9][10][11][12][13]. Vener et al [10] studied theoretically multidimensional proton tunneling in tropolone by using adiabatic separation of variables.…”
Section: Introductionmentioning
confidence: 99%
“…Other systems for which tunnelling have been studied include malonaldehyde [14][15][16][17], formic acid [18], hydrogen-oxalate anion [16], substituted tropolone [19,20] and 5-methyl-9-hydroxyphenalenone (OH and OD) [21], methanol tetramer [22] and hydrogen carbonate dimer ion [23]. Recently a mixed quantum-classical approach has been used to study dynamics of hydrogen-bonded systems [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In the lowest energy configuration the two OH bonds point in opposing directions. Resolved spectral tunneling structures similar to those of the parent TRN(OH) and TRN(OD) molecules are observed for the aforementioned molecules, as well as others: 5-methyl-tropolone [53,54], isopropyltropolones [55], and 5-phenyl-tropolone [56][57]. The effects of coupling the OH_O coordinates to the methyl internal rotation, or of coupling them to the low frequency phenyl torsional motions, are of interest.…”
Section: Discussionmentioning
confidence: 90%
“…The topography of its PES has saddle-point (SP) energy barriers just low enough, and tautomer-to-tautomer heavy atom excursions that are just short enough, to produce numerous resolvable vibrational state-specific coherent tunneling splittings. They are also observed in the 2 H [40,41] and 18 O [39, 42, 43] isotopomers of gaseous TRN, and in simple chemical derivatives [44][45][46][47][48][49][50][51][52][53][54][55][56][57]. The numerous van der Waals complexes of tropolone are not discussed in this chapter.…”
Section: Introductionmentioning
confidence: 99%
“…Tropolone with its intramolecular hydrogen bond is a model substance for studying tunneling process in the ground as well as in the excited electronic state [50][51][52][53][54][55][56][57][58][59]. The geometry of tropolone is presented in Figure 4.…”
Section: Introductionmentioning
confidence: 99%